Socio-Political Communication in Fan Communities: Network Resources in Regional Siberian Sports Fan Communities - Evgeny V. Golovatsky; Pavel B. Gvozdilov (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Fan communities are a socio-political resource capable of mobilizing public initiatives and movements, especially on the regional scale. Research interest in sports fan communities is steadily growing because the fan movement has established itself as a political force. Using the methods of digital footprint analysis, parsing, and review, the authors studied the socio-political communication between fans and the fan environment of Siberian regional online communities. The regional sports fan communities have a separate fan environment, with a specific sports choice and socio-political agenda. Siberian sports fan communities are poorly differentiated but strongly associated with a particular sport, team, or club. Their visual and verbal network communication is not politically-loaded and covers a wide range of topics and events. The content is domineered by reposts, comments and discussions being its minor part. Further qualitative research may identify the social niche of sports fan communities in the life of regions and mono-territories.